Association of dietary fatty acid intake with hypertension in children and adolescents: evidence from the NHANES 2005–2018 - Li, Xiumin; Qi, Fengqin; Zhao, Zhihong; Ma, Jinbang (Frontiers in Pediatrics, 2023)
Aim: To evaluate the association between dietary fatty acid intake and hypertension in children and adolescents. Methods: The National Health and Nutrition Examination Survey (NHANES) 2005-2018 provided data on children and adolescents aged 8-17 years for this cross-sectional study. Dietary total fat and fatty acid intake was evaluated via two 24-hour dietary recall interviews. Multivariate logistic regression models were used to explore the association between fatty acid intake and hypertension, with odds ratios (ORs) and 95% confidence intervals (CIs) calculated. Subgroup analysis was performed according to gender, age and body mass index (BMI) Z-score. Results: This study included 13330 subjects. There were 11614 individuals without hypertension and 1716 with hypertension. Higher intake of total polyunsaturated fatty acids (PUFAs) was associated with significantly lower odds of hypertension (OR = 0.85, 95%CI: 0.74 to 0.97, P = 0.018). No significant associations were found between density of total saturated fatty acid (SFAs), monounsaturated fatty acids (MUFAs) and PUFAs and the odds of hypertension (all P > 0.05). Increased intake of omega-3 (OR = 0.82, 95%CI: 0.72 to 0.93, P = 0.002) and omega-6 (OR = 0.86, 95%CI: 0.75 to 0.98, P = 0.025) PUFAs, octadecatrienoic acid (OR = 0.82, 95%CI: 0.72 to 0.93, P = 0.003) and octadecadienoic acid (OR = 0.86, 95%CI: 0.75 to 0.98, P = 0.025) was associated with significantly reduced odds of hypertension, and individuals with higher omega-6:omega-3 ratio had significantly greater odds of hypertension (OR = 1.09, 95%CI: 1.02 to 1.17, P = 0.025). Density of omega-3 PUFAs (OR = 0.86, 95%CI: 0.78 to 0.95, P = 0.004) and octadecatrienoic acid (OR = 0.87, 95%CI: 0.78 to 0.96, P = 0.006) was inversely associated with the odds of hypertension, and omega-6:omega-3 ratio was positively associated with the odds of hypertension (OR = 1.09, 95%CI: 1.02 to 1.17, P = 0.012). Conclusions: Total PUFA intake was negatively associated with the odds of hypertension in children and adolescents. Higher intake of omega-3 and omega-6 PUFAs, octadecatrienoic acid and octadecadienoic acid as well as density of omega-3 PUFAs and octadecatrienoic acid was associated with the lower odds of hypertension.